The effectiveness of using the means of animated films Upin & Ipin to absorb the vocabulary of students at the Islamic Middle School Yasini Pasuruan: ÙØ¹Ø§Ù„ÙŠØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ø£ÙÙ„Ø§Ù… Ø§Ù„Ù…ØªØØ±ÙƒØ© Ø£ÙˆØ¨ÙŠÙ† ÙˆØ¥ÙŠØ¨ÙŠÙ† Ù„Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø¨Ø© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ÙŠØ§Ø³ÙŠÙ†ÙŠ Ø¨Ø§Ø³Ø±ÙˆØ§Ù† - Muhammad Hasan, Qurrotul Aini, Luâ€™luil Masruroh, (INTAJUNA : Jurnal Hasil Pemikiran, Penelitian, Produk Bidang Pendidikan Bahasa Arab, 2023)
Vocabulary is an essential part of language learning, because the essence of language is a set of vocabulary. Vocabulary is one of the most important linguistic elements that a person must possess in learning a foreign language as well as the Arabic language. Vocabulary education requires appropriate and interesting teaching aids, including animated films. Animated film is one of the means of education that can be applied in education because it can make it easier for students to master vocabulary. The researchers chose a famous figure in Indonesia, Aubin and Eben. The aim of this research is to measure the effectiveness of the use of the means of animated films Openen and Eben to comprehend the vocabulary of students at the Islamic Middle School Yasini in Sarwan. The entrance to this research is the quantitative approach and the type of research is experimental research in two groups. The method of collecting research in this research is testing and documentation. As for the community of this research, all students in the eighth semester and appointed by all the students in the eighth semester A, numbering 32 students. In analyzing the data, the researchers used the 22nd census program with the T test. The result of this research is: the result of the calculation T = 3,079, and the result of the table T = 2.04. The result of the calculation is greater than the result of the tables T, so the yield is no there is a difference between before the use of animated films Open, Eben and Epin. The data shows that the use of animated films Openen and Eben to absorb the vocabulary of students at the Islamic Middle School Yasini Pauruan is effective keyyword: animated films Aubin and Eben, vocabulary comprehension